Analisis Persepsi Ibu Balita Terhadap Layanan Posyandu - Rahmi, Vrisca; Azhar, Azhar; Jais, Muhammad (Program Studi Pendidikan Luar Sekolah, 2025)
Abstract: The purpose of this study was to analyze the level of perception of mothers of toddlers towards Posyandu Anggrek services in Kampung Perawang Indah, Tualang District, Siak Regency. The method in the study used a quantitative approach with a descriptive survey design. The study population amounted to 107 mothers of toddlers with a sample of 85 respondents determined through simple random sampling technique. Instruments used in this study through a structured questionnaire based on five indicators used (Reliability, responsiveness, empathy, physical evidence and assurance). Instrument validity was tested using item-total correlation analysis and reliability using Cronbach's Alpha. Data analysis techniques used descriptive statistics and One Sample t-test. This study shows that the level of perception of mothers of toddlers towards posyandu services is in the “High” category (mean = 4.05) or the average score value is 81.30. Hypothesis testing using One Sample t-test shows the level of satisfaction of mothers of toddlers is significantly higher than the standard value (t=42.049; p>0.05). This study contributes to the development of knowledge about the quality of community-based primary health care and provides practical implications for improving posyandu services.Key Words: Health Service Quality, Patient Satisfaction, Posyandu, Maternal and Child HealthAbstrak: Tujuan dari penelitian ini untuk menganalisis tingkat persepsi ibu balita terhadap layanan Posyandu Anggrek di Kampung Perawang Indah, Kecamatan Tualang, Kabupaten Siak. Metode dalam penelitian menggunakan pendekatan kuantitatif dengan desain survei deskriptif. Populasi penelitian berjumlah 107 ibu balita dengan sampel sebanyak 85 responden yang ditentukan melalui teknik simple random sampling. Instrumen yang digunakan dalam penelitian ini melalui kuesioner terstruktur berdasarkan lima indikator yang digunakan (Reliabilitas, daya tanggap, empati, bukti fisik dan jaminan). Validitas instrumen diuji menggunakan analisis korelasi item-total dan reliabilitas menggunakan Cronbach's Alpha. Teknik analisis data menggunakan statistik deskriptif dan One Sample t-test. Penelitian ini menunjukkan bahwa tingkat persepsi ibu balita terhadap layanan posyandu berada pada kategori